Entrapment - conceito, definição e características psicométricas da versão portuguesa da Escala de Entrapment - Carvalho, Serafim (2011)
The role of evolutionary strategies in psychopathology has been widely studied in recent years, particularly the mechanisms of fight and flight. Entrapment means the inhibition of escape strategy when it’s psychobiologically activated. Life contexts with characteristics of entrapment are linked to stress, anxiety, depression and suicide. This work presents the psychometric characteristics of the Entrapment Scale (ES) originally developed by Gilbert & Allan (1998). It consists of two scales: the Internal Entrapment Scale (IES) related to activation to escape, motivated by aversive emotional states and External Entrapment Scale (EES), when the desire to escape is stimulated by external events. The scale was evaluated in three samples: students (N = 608), general population (N = 406) and depressed patients (N = 106). The scale reproduces the results of their authors. It has demonstrated high internal consistency, with Cronbach α ranging between .85 and .93, one-dimensional structure for each scale and the extracted factors explain between 50.9% and 67.6% of total variance. Temporal stability was moderate to high (r = .66 to r = .92). Patients have significantly higher values on the IES and the EES than controls, supporting the construct validity. The moderate correlations (r = .50 to r = .64) between EE and the Beck Depression Inventory suggest a convergence between these instruments. Entrapment Scale has good psychometric characteristics, and must now broaden its application on studies of prospective nature in clinical settings.